Comparative Study to Assess the Knowledge on Worm Infestation among Urban and Rural Mothers of School Going Children (3-12 Yrs) at Karaikal District (Medico Legal Update, 2020)
Background: Helminthes infections are more prevalent among school children aged 5-14 years. Hookwormburden is the major etiology for iron deficiency anemia in young children. One of the major health concernsespecially among children is anemia and malnutrition. This risk has further complicated by lack of awarenesson prevention of worm infestation among children and parents, care givers especially mothers. Increasingchildren’s and their Parents awareness of the problem can help to fight the disease.Objectives: To assess the knowledge on worm infestation among urban and rural mothers of School goingchildren.Materials and Method: Non-experimental Comparative study was conducted to assess the knowledgeamong mothers in urban and rural area at Karaikal. Sample size comprised of 150 mothers of school goingchildren were selected through non-probability or non-randomized convenience sampling. Out of 150mothers 75 mothers from urban area and 75 mothers from rural area. The data was collected by using pretestedstructured knowledge questionnaire. Data was analyzed by both descriptive and inferential statistics.Results: This study revealed that in urban area the majority of the mothers of school going children 37%(28)had adequate knowledge, 40%(30) had moderately adequate knowledge and 23%(17) had inadequateknowledge regarding worm infestation. Also revealed that in rural area the majority of the mothers of schoolgoing children 35%(26) had inadequate knowledge, 36%(27) had moderately adequate knowledge and29%(22) had adequate knowledge regarding worm infestation. Mean and standard deviation (SD) of theurban and rural area mothers of school going children respectively 16.8±4.77, 15.01±5.16.Conclusion: The researcher concluded that the need for more research to improve not only the knowledgealso attitude and practices among mothers of school age children on worm infestations.